2006
DOI: 10.1074/jbc.m509422200
|View full text |Cite
|
Sign up to set email alerts
|

Docking Studies Show That D-Glucose and Quercetin Slide through the Transporter GLUT1

Abstract: On a three-dimensional templated model of GLUT1 (Protein Data Bank code 1SUK), a molecular recognition program, AUTODOCK 3, reveals nine hexose-binding clusters spanning the entire "hydrophilic" channel. Five of these cluster sites are within 3-5 Å of 10 glucose transporter deficiency syndrome missense mutations. Another three sites are within 8 Å of two other missense mutations. D-Glucose binds to five sites in the external channel opening, with increasing affinity toward the pore center and then passes via a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
0
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 44 publications
7
83
0
2
Order By: Relevance
“…Substitutions at Y293 in this loop impair transport activity by reducing accessibility to the cytoplasmic substratebinding site, effectively locking the transporter into an outward facing conformation (11). The T295 amino acid residue is about 4.9 Å away from one of the nine clusters spanning the entire hydrophilic channel as revealed by docking studies (37) and locates along the extracellular opening of the transport channel (35). Mutagenesis studies of the T295A, T295S, and T295G Glut-4 mutants (amino acid residue corresponding to that of Glut1 in COS-7 cells) showed that T295A abolishes the glucose transport activity and markedly reduces the Cytochalasin B binding without affecting the photolabeling with ATB-BMPA.…”
Section: Discussionmentioning
confidence: 99%
“…Substitutions at Y293 in this loop impair transport activity by reducing accessibility to the cytoplasmic substratebinding site, effectively locking the transporter into an outward facing conformation (11). The T295 amino acid residue is about 4.9 Å away from one of the nine clusters spanning the entire hydrophilic channel as revealed by docking studies (37) and locates along the extracellular opening of the transport channel (35). Mutagenesis studies of the T295A, T295S, and T295G Glut-4 mutants (amino acid residue corresponding to that of Glut1 in COS-7 cells) showed that T295A abolishes the glucose transport activity and markedly reduces the Cytochalasin B binding without affecting the photolabeling with ATB-BMPA.…”
Section: Discussionmentioning
confidence: 99%
“…Recent docking studies have suggested that GLUT1 presents two exofacial and endofacial glucose-binding sites connected by a cavity sufficiently large to contain a glucose molecule (27,109). It should be noted, however, that homology modeling is not immune to overinterpretation.…”
Section: Unifying Model For Structure and Transportmentioning
confidence: 99%
“…The homology-modeled GLUT1 structure (109) closely resembles GlpT and LacY structures. (11); red, amino acids, which when mutagenized to cysteine are reactive with PC-MBS in the external solvent (94); green, amino acids, which when mutagenized to cysteine are reactive with p-chloromercuribenzylsulfonic (PCMBS) in the external solvent in a substrate-protected manner (94); yellow, cysteine residues that are accessible to iodoacetamide (11); purple, amino acids, which when mutagenized to cysteine result in Ն90% inhibition of GLUT1 (94); orange, putative substrate-binding sites predicted by docking studies (27,109); blue, amino acids implicated in substrate discrimination (87); black, sites at which mutations cause GLUT1 deficiency syndrome (68,124). Some amino acids fall into multiple categories.…”
Section: Glut1 Topology and Architecturementioning
confidence: 99%
See 1 more Smart Citation
“…This transport process may be further complicated in that many PCs present in plants are linked to sugar moieties, which may have an impact on their oral absorption. For example, there is in vitro and in silico evidence that the human glucose transporter 1 (SLC2A1) and rat glucose transporter 4 (slc2a4) transports quercetin (Strobel et al, 2005;Cunningham et al, 2006). In addition, the pig but not human sodium-dependent glucose transporter-1 (SGLT1) appeared to be involved in the intestinal uptake of quercetin glucosides (Cermak et al, 2004;Kottra & Daniel, 2007).…”
Section: Absorption From Gastrointestinal (Gi) Tractmentioning
confidence: 99%